Baseline Demographics, Rationale, and Methods of Jiri Eye Disease Incidence Study - Thapa, Suman Shumsher; Joshi, Anup Raj; Poudel, Manish; Banjara, Pradeep; Shrestha, Mohan Krishna; Khanal, Shankar Prasad; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2024)
Introduction: Anthropological and biomedical studies have been undertaken in the Jirel population for more than three decades. The Jirel pedigree is one of the most powerful documented human pedigree’s currently available for genetic studies. Objective: To estimate the incidence of cataract, glaucoma and retinal diseases among the Jirel population aged 50 years or more over a period of 10 years. Methodology: Jiri Eye Disease Incidence Study (JEDIS) is population-based cohort study that will enroll all participants of Jiri Eye Study (JES) aged 50 years and above, once every four years up to the year 2028. Detailed clinical examinations and investigations following the same clinical protocols of the JES will be carried out. Result: Baseline demographics of 690 participants aged 50 years and above revealed 50.4% were males and 49.6% females and the average age (standard deviation) was 61.5 (8.6) years for males and 62.2 (8.7) years for females. At the end of 5 years, 483 participants completed the follow up, a response rate of 80%. Conclusion: Epidemiological information derived from this study will help understand the natural history of eye diseases and implement health care programs for the prevention of blindness in the Jirel population.